Effects of Crowding and Wave Exposure on Cirrus Morphology of the Acorn Barnacle, Semibalanus balanoides - Hoch, J. Matthew (NSUWorks, 2011)
Wave action and density dependent effects can strongly affect the ability of sessile barnacles to feed and assimilate energy. Phenotypic plasticity in cirrus form has been demonstrated in several species of acorn barnacles in response to those factors. Field experiments were used to test whether cirrus morphology of the North Atlantic acorn barnacle, Semibalanus balanoides, varied in sites over a gradient of wave-exposure or in aggregations manipulated for population density and neighborhood size. Variation in morphology of the feeding cirri differed between sites, but was not directly related to estimates of wave exposure. This may have been a result of altered feeding behavior in different types of flow. Cirrus morphology did not vary with either aggregation size or density. This study identifies variation in cirrus form for S. balanoides, suggests its dependence on the hydrodynamic environment and lack of dependence on density.